Coronary heart disease risk in patients with stroke or transient ischemic attack and no known coronary heart disease: findings from the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) trial - Amarenco, Pierre; Goldstein, Larry B.; Sillesen, Henrik; Benavente, Oscar; Zweifler, Richard M.; Callahan, Alfred; Hennerici, Michael G.; Zivin, Justin A.; Welch, K. Michael A. (Stroke, 2010)
Background and Purpose: Noncoronary forms of atherosclerosis (including transient ischemic attacks or stroke of carotid origin or >50% stenosis of the carotid artery) are associated with a 10-year vascular risk of >20% and are considered as a coronary heart disease (CHD) -risk equivalent from the standpoint of lipid management. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) trial included patients with stroke or transient ischemic attack and no known CHD regardless of the presence of carotid atherosclerosis. We evaluated the risk of developing clinically recognized CHD in SPARCL patients.Methods— A total of 4731 patients (mean age, 63 years) was randomized to 80 mg/day atorvastatin placebo. The rates of major coronary event, any CHD event, and any revascularization procedure were evaluated.Results— After 4.9 years of follow-up, the risks of a major coronary event and of any CHD end point in the placebo group were 5.1% and 8.6%, respectively. The rate of outcome of stroke decreased over time, whereas the major coronary event rate was stable. Relative to those having a large vessel-related stroke at baseline, those having a transient ischemic attack, hemorrhagic stroke, small vessel stroke, or a stroke of unknown cause had similar absolute rates for a first major coronary event and for any CHD event; transient ischemic attack, small vessel, and unknown cause groups had lower absolute revascularization procedure rates. Major coronary event, any CHD event, and any revascularization procedure rates were similarly reduced in all baseline stroke subtypes in the atorvastatin arm compared with placebo with no heterogeneity between groups.Conclusion— CHD risk can be substantially reduced by atorvastatin therapy in patients with recent stroke or transient ischemic attack regardless of stroke subtype.
Gesehen am 17.03.2021